مسلکی کشمکش کے تدارک کی عملی صورتیں: سیرت النبیﷺ کا اختصاصی مطالعہ: PRACTICAL WAYS TO RESOLVE SECTARIAN CONFLICT: A SPECIAL STUDY OF THE BIOGRAPHY OF THE PROPHET MUHAMMAD (PBUH) (Al-Aasar, 2025)
A study of the biography of the Prophet (peace be upon him) illustrates the fact that the Holy Prophet (peace be upon him) united people of different tribes, classes and backgrounds, and instilled in their hearts a spirit of love, tolerance and mutual respect. A diverse society was established in Medina where Jews, Christians, polytheists and Muslims of different tribes lived in peace and respect under a common social contract (the Covenant of Medina). The biography of the Prophet (peace be upon him) teaches us that differences are not turned into contradictions but rather learned to live with them. Among the internal challenges facing the Muslim Ummah in the present era, sectarian strife and sectarian conflicts are prominent. This conflict is not only tearing apart the unity of the Ummah but also hindering the peaceful and universal message of Islam. In the current circumstances, it is imperative to find a practical solution to this problem. The aim of this research is to identify practical principles and measures in the light of the life of the Holy Prophet (peace and blessings of Allah be upon him) through which sectarian differences can be limited and mutual tolerance can be promoted. This paper concludes that if the Muslim community makes the biography of the Prophet Muhammad (peace be upon him) a part of their individual and collective lives, rather than limiting it to mere study, then it is possible to end sectarian conflict. The biography of the Prophet (peace be upon him) is not only a source of intellectual guidance but also a manifestation of practical wisdom, which shows us the path to unity despite mutual differences.